Burza mózgów w dydaktyce – (nie)potrzebny chaos - Cybulska-Wal, Alina (Dydaktyka Polonistyczna, 2016)
Research on brainstorming in school has demonstrated that almost all of the implemantationsare done wrong because of the social and organisational errors. Alina Cybulska-Wal proposes tounderstand the main idea of brainstorming as the SOE triade: where Satisfaction, Organizing andEfficiency have an influence on each other. Sollutions mentioned in this article define what the problem of „brainstorming in school” is and help to run rewarding creative sessions.